Analisis Pengaruh Penerapan Standar Akuntansi Keuangan (SAK) Terhadap Transparansi Keuangan Usaha Kost di Kota Sukaharjo - Widodo, Eko Widyanto; Kusuma, Indra Lila; Suprihati, Suprihati (CV. Rayyan Dwi Bharata, 2025)
This study aims to analyze the influence of the implementation of financial accounting systems on financial transparency in small to medium-scale boarding house businesses in Sukaharjo City, using a quantitative research approach with a descriptive nature. The data collection technique involved distributing questionnaires to a sample of 88 respondents who are boarding house business owners in Sukaharjo City, as well as using observation sheets and documentation. Based on the analysis results, it can be concluded that the implementation of Financial Accounting Standards (SAK) has a positive and significant impact on financial transparency in the boarding house businesses in Sukoharjo. The implementation of SAK was found to partially affect financial transparency, thus confirming the hypothesis that such an effect exists. Furthermore, the analysis results show that the implementation of SAK can explain a significant portion of the variation in financial transparency, which amounts to 98.3%. Therefore, the implementation of SAK plays a crucial role in improving the financial transparency of boarding house businesses. However, there are other factors outside the variables studied that also contribute to financial transparency.